2012
DOI: 10.3171/2011.8.spine11272
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter validation of a formula predicting postoperative spinopelvic alignment

Abstract: Object Sagittal spinopelvic imbalance is a major contributor to pain and disability for patients with adult spinal deformity (ASD). Preoperative planning is essential for pedicle subtraction osteotomy (PSO) candidates; however, current methods are often inaccurate because no formula to date predicts both postoperative sagittal balance and pelvic alignment. The authors of this study aimed to evaluate the accuracy of 2 novel formulas in predicting postoperative spinope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 21 publications
3
30
0
1
Order By: Relevance
“…The global lumbar lordosis in our group improved by 24 degrees, from 24 to 48 degrees, while segmental lordosis at the levels where an ALR was performed improved an average of 17 degrees. Given that the SVA improved by 4.9 cm, from 9 to 4.1, and within the range established by Lafage et al, we expect postoperative outcome scores to be improved [40, 41]. This is in fact the case, as VAS and ODI scores improved by 26 and 18%, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…The global lumbar lordosis in our group improved by 24 degrees, from 24 to 48 degrees, while segmental lordosis at the levels where an ALR was performed improved an average of 17 degrees. Given that the SVA improved by 4.9 cm, from 9 to 4.1, and within the range established by Lafage et al, we expect postoperative outcome scores to be improved [40, 41]. This is in fact the case, as VAS and ODI scores improved by 26 and 18%, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…However, recent studies have clearly shown that PI- LL mismatch is among the key radiographic parameters associated with pain and disability among adults with spinal deformity. 1,17,18,21,25,27,31,34,43 The study reported here demonstrated that patients with compensated flatback syndrome can have significant pain and disability at baseline and that surgical correction can lead to similar radiographic and HRQOL improvements for these patients as for those with pathologically elevated SVA. Collectively, these findings demonstrate that evaluation of sagittal spinal alignment should extend beyond measuring SVA and that PI-LL mismatch among patients with concordant pain and disability can be considered a primary indication for surgery with the potential for significant improvement of HRQOL.…”
Section: Discussionmentioning
confidence: 67%
“…3,7,21,22,[25][26][27][28][29][30][31][35][36][37][38][39]41,44,45,48,51,52 Although patient-related factors, including BMI, depression, and baseline levels of pain and disability, seemed to dominate the distinguishing factors between best and worst outcomes, sagittal spinopelvic alignment parameters were also evident. Residual positive sagittal malalignment (SVA) was a significant distinguishing factor on multivariate analysis, which is consistent with previous reports that have documented negative impact of elevated SVA on HRQOL.…”
Section: Discussionmentioning
confidence: 99%